(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Knowledge management (KM) is the process of capturing,developing, sharing & effectively using organizational knowledge. It refersto a multi-disciplined approach to achieving or organizational objectives bymaking the best use of knowledge.